PERANCANGAN VISUAL BRANDING KOTA PADANG PANJANG - HUMAIRA, San Ahdi, S.Sn., M.Ds., Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Padang Panjang is a city with the smallest area in West Sumatra. Padang Panjang has many potential ranging from education, food, travel to industrial products. Until now the potential of Padang Panjang is not so well known and recognized by the public due to lack of promotion of the city government. The reason is the underlying design of visual branding.The analytical method chosen in the design of visual branding Padang Panjang are SWOT (Strengths, Weakness, Opportunities, Threat) method is used to find weaknesses, strengths, opportunities, and threats Padang Panjang as well as a differentiating factor with competitors city.Results of visual design branding for Padang Panjang are logo and tagline that is applied to the main form of guidebooks brand Padang Panjang and stationery sets such as business cards, folders, cd cover and cd, letterhead fiber and envelopes and notebooks as well as supporting media include billboards, T-shirts, totebag, clocks, stickers, hats and umbrellas.Keywords: Visual branding, Padang Panjang, Logo, Billboard.